Capacitive deionization in organic solutions: case study using propylene carbonate. Issue 7 (13th January 2016) - Porada, S.; Feng, G.; Suss, M. E.; Presser, V.
Abstract : We present a study of the performance of capacitive deionization (CDI) when applied to electrosorption in an organic solvent, finding enhanced cell charging voltages and improved salt sorption over electrosoprtion in aqueous solutions. Abstract : Capacitive deionization (CDI) is an emerging technology for the energy-efficient removal of dissolved ions from aqueous solutions. Expanding this technology to non-aqueous media, we present an experimental characterization of a pair of porous carbon electrodes towards electrosorption of dissolved ions in propylene carbonate. We demonstrate that application of CDI technology for treatment of an organic solution with an electrochemical stability window beyond 1.2 V allows for a higher salt removal capacity and higher charge efficiency as compared to CDI applied for treatment of aqueous electrolytes. Further, we show that using conductivity measurements of the stream emerging from the CDI cell combined with an equilibrium electric double-layer structure model, we can gain insights into charge compensation mechanisms and ion distribution in carbon nanopores.